2016
DOI: 10.3847/0004-637x/825/1/16
|View full text |Cite
|
Sign up to set email alerts
|

Wide Field Co Mapping in the Region of Iras 19312+1950

Abstract: We report the results of a wide field CO mapping in the region of IRAS 19312+1950. This IRAS object exhibits SiO/H 2 O/OH maser emission, and is embedded in a chemically-rich molecular component, of which the origin is still unknown. In order to reveal the entire structure and gas mass of the surrounding molecular component for the first time, we have mapped a wide region around IRAS 19312+1950 in the 12 CO J = 1-0, 13 CO J = 1-0 and C 18 O J = 1-0 lines using the Nobeyama 45m telescope. In conjunction with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 90 publications
2
12
0
Order By: Relevance
“…Considering this as R 0 , we obtain the stellar velocity v * as 6.2 km s −1 . Typical stellar velocities observed in bow shock regions are ∼10 km s −1 (van Buren & Mac Low 1992;Nakashima et al 2016) which is similar to our estimate. The arc-shaped emission is also symmetric around MIR31.…”
Section: S2supporting
confidence: 90%
“…Considering this as R 0 , we obtain the stellar velocity v * as 6.2 km s −1 . Typical stellar velocities observed in bow shock regions are ∼10 km s −1 (van Buren & Mac Low 1992;Nakashima et al 2016) which is similar to our estimate. The arc-shaped emission is also symmetric around MIR31.…”
Section: S2supporting
confidence: 90%
“…In Figure 11, we plot the FWZPs of the SiO J=1-0 and H 2 O maser lines averaged for observational epochs except for IRAS 19312+1950. As previously mentioned, the maser source of IRAS 19312+1950 seems to be a red supergiant associated with its natal cloud rather than an AGB or post-AGB star (Nakashima et al 2016). In Table 10, we present averaged FWZPs and their ratios between SiO J=1-0 and H 2 O maser lines for target sources in order of FWZPs.…”
Section: Maser and Infrared Properties Associated With A Post-agb Stamentioning
confidence: 93%
“…Therefore, this object presented a duality of a young stellar object in a starforming region and an evolved star (Nakashima et al 2011). Recently, Nakashima et al (2016), based on the derived mass of the molecular components and the large luminosity, suggested that the maser source of IRAS 19312+1950 seems to be a red supergiant associated with its natal cloud rather than an AGB or post-AGB star.…”
Section: Iras 19312+1950mentioning
confidence: 99%
“…Optical spectroscopy of the massive hypergiant IRC +10420 also found a similar nitrogen enhancement factor to A-type supergiants (Klochkova et al 1997). The en-40 CH 3 OH has only been detected (recently) towards two evolved stars and one evolved star candidate thus far, including the post-AGB object HD 101584 (Olofsson et al 2017), the YHG IRC +10420 at marginal S/N ratios (Quintana-Lacaci et al 2016), and the peculiar object IRAS 19312+1950 (Nakashima et al 2015), which is located in a complex region that contains dense interstellar gas (see also Nakashima et al 2016;Cordiner et al 2016).…”
Section: Ammonia Chemistrymentioning
confidence: 78%